“We’ve always been interpreters”: the identities and roles of indigenous interpreters in the peruvian judicial system - Shimabukuro, Bryan Matayoshi (2022)
This article analyses the perspectives of a group of indigenous language interpreters regarding interpreting in Peru’s judicial system. Semi-structured interviews were held with eight interpreters of different indigenous languages, who recounted how they acquired both their own people’s and the Spanish languages, their professional activities, their processes of insertion into national language policies and their views on the power relationships evinced in their work with the State and, more specifically, within the judicial system. It outlines participants’ viewpoints regarding their relationship with the indigenous communities who are the recipients of language services and with justice system actors. These interactions construct different identitary dimensions amongst interpreters, whilst also impacting their understanding of their roles and status.